Siplizumab, an Anti-CD2 Monoclonal Antibody, Induces a Unique Set of Immune Modulatory Effects Compared to Alemtuzumab and Rabbit Anti-Thymocyte Globulin In Vitro - Binder, Christian; Sellberg, Felix; Cvetkovski, Filip; Berglund, Erik; Berglund, David (Frontiers in Immunology, 2020)
Monoclonal antibodies are used in organ transplant induction therapy and to treat autoimmune disorders. The effects of biologics on the human immune system remain incompletely characterized and a deeper understanding of their mechanisms of action may provide useful insights for their clinical application. The goal of this study was to contrast the mechanistic properties of siplizumab with Alemtuzumab and rabbit Anti-Thymocyte Globulin (rATG). Mechanistic assay systems investigating antibody-dependent cell-mediated cytotoxicity, antibody-dependent cell phagocytosis and complement-dependent cytotoxicity were used to characterize siplizumab. Further, functional effects of siplizumab, Alemuzumab and rATG were investigated in allogeneic mixed lymphocyte reaction. Changes in T cell activation, T cell proliferation and frequency of naïve T cells, memory T cells and regulatory T cells induced by siplizumab, Alemtuzumab and rATG in allogeneic mixed lymphocyte reaction were assessed via flow cytometry. Siplizumab depleted T cells, decreased T cell activation, inhibited T cell proliferation and enriched naïve and bona fide regulatory T cells. Neither Alemtuzumab nor rATG induced the same combination of functional effects. The results presented in this study should be used for further in vitro and in vivo investigations that guide the clinical use of immune modulatory biologics.